TIP41 network analysis and mutant phenotypes predict interactions between the TOR and ABA pathways. (2nd December 2018) - Punzo, Paola; Ruggiero, Alessandra; Grillo, Stefania; Batelli, Giorgia
ABSTRACT: Environmental conditions inform the rate of plant growth and development. The target of rapamycin (TOR) signalling pathway is a central regulator of plant growth in response to nutrients and energy, while abscisic acid (ABA) is a main mediator of abiotic stress responses. We recently characterized Arabidopsis TIP41, a predicted TOR pathway component involved in the ABA-mediated response to abiotic stress. Here, we report the ABA sensitivity of tip41 mutants, supporting the relation between TIP41 and the hormone pathway. The analysis of predicted TIP41 functional network identified several protein phosphatases. In particular, candidate protein interactors included catalytic subunits of type 2A protein phosphatases and protein phosphatases 6, which regulate different developmental processes and responses to environmental stimuli. These results provide important information on the role of TIP41 in the cross talk between TOR and ABA pathways.